Study Protocol for the SC-SD4ASA Project: A Self-Care/Self-Development Guidebook for Asylum-Seeking Adolescents - Mohammadzadeh, Marjan; Heinrichs, Katherina; Pilz González, Laura; Stock, Christiane (Frontiers in Public Health, 2022)
From 2015 to 2016, about 1.3 million refugees arrived in Europe. Half of them were children under the age of 18. The combination of (specially forced) migration and adolescence increase the risk of psychological problems among refugees including asylum-seeking children and adolescents. Therefore, along with the significant increase in the number of refugees, investigating effective ways to improve their health status has grown. The planned project aims to improve self-care and self-development among asylum-seeking adolescents aged 15 to 18. With the long-term goal of improving well-being and quality of life, this multi-method study aims to develop a self-care and self-development intervention guideline for asylum-seeking adolescents. The SC-SD4ASA project will focus on three main work packages: 1. assessment of needs and knowledge concerning self-care and self-development; 2. development of a guidebook to promote self-care and self-development for asylum-seeking adolescents and 3. assessment of the guidebook fidelity, reliability, and validity. For the first work package, an intra-triangulation approach including three qualitative methods (in-depth interviews, focus group discussions and photographic means (photovoice)) will be used. The data collected will be analyzed using the cross-cultural and multilingual approach to thematic analysis known as meta-theme analysis. The results of the first stage will be utilized for developing the guideline in the second (main) work packages. The guideline fidelity will be assessed based on the National Institutes of Health Behavior Change Consortium fidelity framework in the last workplan. Empowering asylum-seeking adolescents with self-care /self-development skills can help them to sustain their well-being and better manage the challenges in their new situation. When successfully implemented, a guideline will be developed to support all individuals involved in planning, managing, and promoting health among asylum-seeking adolescents that can be used for future self-care/self-development programs in practice.